(untitled) (Research, Society and Development, 2020)
The construction of a network of action between the State and civil society is a point that requires a lot of attention when discussing local development strategies. In the Brazilian case, the theme has constitutional importance when observing that the creation of a solidary society is one of the fundamental objectives of the Republic. Despite this, there is still a low Brazilian academic production on the topic of networks between the public power and private non-profit institutions. Thus, in this work, the objective is to identify theoretical works in this field through a bibliographic survey of national literature. For this, an analysis of citations of academic works is made, through which delimitations are made to concentrate on the theme of creating networks between the public and private sectors. As a result, it is indicated in this work that national productions found have a focus on assessing the effects of networks on the development of affected communities, such as the empowerment of the group of direct actors and modification of state actions by the influence of the established partnership relationship, on the other hand, theoretical production on the configuration of these networks is still low